The Influence of Language Interest on Foreign Language Learning Outcomes (Arabic-English) in Immersion-Based Learning at the Modern Islamic Boarding School in South Tapanuli - Amin, Irsal; Pulungan, Muhammad Yusuf; Ritonga, Sylvia Kurnia (Borneo Journal of Language and Education, 2026)
High student interest and motivation in learning a foreign language do not guarantee high language learning outcomes, because many factors influence the outcomes as additional variables. This study aims to explain the influence of language interest on foreign language learning outcomes through the formation of a language environment. If previous studies explain that interest influences learning outcomes, then this study tries to see the influence of interest on learning outcomes that do not stand alone, but there are other factors that also influence such as biah lughah. This research is quantitative research with data collection techniques through questionnaires, tests, and interviews. The population of this study consisted of 380 students, while the sample was 141 students with an accidental sampling model. After the research data were collected, they were analyzed using descriptive statistics (frequency, percentage, and mean). The study found that Arabic language learning was implemented through an immersion strategy, including daily activities, language weeks, and integrative learning between furu'iyah and wahdah. Most students showed greater interest in Arabic (73.05%) compared to English (46.8%). This suggests that the language of instruction significantly impacts language interest, with Arabic being more relevant in the context of Islamic boarding school life. A significant relationship (Sig. 0.002 < 0.005) was found between language interest and learning outcomes, though the contribution was minimal (R2 = 0.04%). This indicates that foreign language learning success is influenced by a combination of intrinsic and extrinsic factors, rather than interest alone.